Consumption of Drinking Water and Its Contribution to Lead (Pb) Exposure in Toddlers Nutritional Status in Indonesia - Muhammad Fadillah; Nuri Andarwulan; Didah Nur Faridah (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2022)
Stunting in toddlers is still occurring in Indonesia. Heavy metals, especially lead (Pb), can cause calcium metabolism disorders. Drinking water has the largest contribution to Pb exposure. The research objective was to conduct a risk assessment of Pb from drinking water in toddlers in Indonesia. The Pb risk assessment was carried out by testing Pb levels in drinking water, extracting consumption data from the Individual Food Consumption Survey in 2014 and Basic Health Research in 2013, calculating Pb exposure, characterizing Pb risk, and predicting the correlation of Pb exposure from drinking water to the toddler nutritional status based on length/height-for-age. The average Pb exposure ranged from 0.026-0.082 μg/kgbw/day and the margin of exposure value ranged from 28.05-8.79 thus the risk of Pb from drinking water for toddlers was low. Correlation value between Pb exposure and the toddler nutritional status based on length/height-for-age in provinces with Pb levels more than limit of detection for children aged 0-11, 12-23, 24-35 and 36-47 months was 0.004; -0.038; -0.109 and -0.231, respectively. The resulting correlation from 0.004 to -0.231 were weak therefore Pb exposure from drinking water is unlikely causing stunting in Indonesian toddlers.